Kinetics of change of descriptions of lubricating material is in the conditions of the insufficient painting - Савчук, А.М. (Problems of Tribology, 2014)
The paper presents results of experimental investigation of the formation of lubricating film and anti-friction properties change lubricants in poor lubrication.Revealed an increase in uniform thickness by rapid activation of the hydrocarbon fractions of lubricant.Found that with increasing speed rolling is enhanced formation thickness of lubricant layer in contact, resulting in increase of anti-friction properties.